Perancangan Sistem Otomatisasi Peternakan Ayam Broiler Berbasis Internet Of Things - Hendra; Maya Indriana; Nurul Tri Artika; Ricca Ismayani; David Jumpa Malem Sembiring; Melvarina Tamba (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
Livestock is an activity to breed and cultivate livestock to get the benefits and results of these activities. Therefore we need a system that is able to help control feeding and drinking and regulate temperature humidity . The technology that can be used is internet of things technology which is a technology that allows physical objects to communicate with each other via the internet. This farm system uses 4 sensors that function to detect temperature, light, feed availability, and drinking availability. and using Arduino 328 as a microcontroller which functions to control an input output from a system designed to process input data from sensors. the test results show that the system is able to provide information through the android application if a vacancy is detected in the feed and drink place as well as temperature humidity control.